Legal Protection for Minors Through Guardianship Institutions - Heriyani, Endang; Yuniarlin, Prihati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The child, as a legal subject, has rights protected from birth, even while in the womb. This is regulated in Article 2 of the Civil Code. Children are considered a group of individuals incapable of legal actions. To engage in legal actions, they must be represented by their parents or legal guardians. Not all children are under the authority of their parents. If both parents passing away, being unable to exercise parental authority, or having parental authority revoked by the court, the child falls under guardianship. This research aims to understand the protection of children through the guardianship institution according to the Civil Code and the Marriage Law No. 1 of 1974. The research follows a normative legal approach, and secondary data is collected through document analysis. The data obtained is analyzed using descriptive methods with a qualitative approach. This research concludes that through the guardianship institution, a guardian takes on the role of the parent in fulfilling all the needs of the child. Several provisions regarding guardianship found in the Civil Code and Marriage Law No. 1 of 1974, which provide protection for children, both in terms of personal and property rights, include: (1) the guardian's obligations, (2) the existence of a supervisory guardian, (3) prohibitions for the guardian, (4) limitations on the guardian's authority, (5) revocation of the guardian's authority, and (6) the guardian's accountability.